Lombalgia com sinais de alarme: um caso de espondilodiscite - Couto, M (2007)
Spondylodiscitis is a serious clinical entity. Despite the decrease in mortality from about 25% in the pre-antibiotic era to near 5%, it remains significant and the associated morbidity is still relevant. The rate of residual neurological deficits among survivors is around 7%. In 30% of patients some related symptoms persist, the most important being pain. The authors report the case of a 74-year-old male patient with recent onset low back pain, which caused considerable disability. With this work the authors intend to alert to the fact that in a patient with a common symptom such as low back pain, the presence of "red flags" requires a quick investigation and diagnosis in order to prevent serious damage.